Effect of atomic under-coordination on the properties of Ag and Cu nanoclusters - Ahmadi, Shideh (2015)
Density functional theory calculations have been carried out to investigate the effect of the atomic under-coordination on the bond contraction, lattice strain, and electron configuration of Cuboctahedral and Marks decahedral structures of silver and copper nanoclusters. Our calculated results are consistent in trend with experimental measurements including extended X-ray-absorption fine structure (EXAFS), scanning tunneling microscope/spectroscopy (STM/S), X-ray photoelectron spectroscopy (XPS), and ultraviolet photoelectron spectra (UPS). This agreement approved the prognostications made on the bond-order-length-strength (BOLS) correlation and nonbonding electron polarization (NEP), suggesting that atomic under-coordination at the surface of nanoclusters cause bond contraction, which then leads to lattice strain, charge densification, core electron entrapment, as well as polarization of valence charge. The results of this work will contribute to the understanding of the intriguing properties of Ag and Cu nanoclusters.